Analytical gradients for subsystem density functional theory within the slater‐function‐based amsterdam density functional program. Issue 4 (2nd December 2016) - Schlüns, Danny; Franchini, Mirko; Götz, Andreas W.; Neugebauer, Johannes; Jacob, Christoph R.; Visscher, Lucas
Abstract : We present a new implementation of analytical gradients for subsystem density‐functional theory (sDFT) and frozen‐density embedding (FDE) into the Amsterdam Density Functional program (ADF). The underlying theory and necessary expressions for the implementation are derived and discussed in detail for various FDE and sDFT setups. The parallel implementation is numerically verified and geometry optimizations with different functional combinations (LDA/TF and PW91/PW91K) are conducted and compared to reference data. Our results confirm that sDFT‐LDA/TF yields good equilibrium distances for the systems studied here (mean absolute deviation: 0.09 Å) compared to reference wave‐function theory results. However, sDFT‐PW91/PW91k quite consistently yields smaller equilibrium distances (mean absolute deviation: 0.23 Å). The flexibility of our new implementation is demonstrated for an HCN‐trimer test system, for which several different setups are applied. © 2016 Wiley Periodicals, Inc. Abstract : A flexible, parallel implementation of analytical gradients for subsystem DFT and frozen‐density embedding is presented. Optimized structures are compared to high‐accuracy reference data.